The violation of fundamental rights in the Peruvian tabloid press. Ojo daily case. - Contreras Martínez, Javier Francisco (2022)
The theme of the present work answers the question: how are fundamental rights violated in the news treatment by the Peruvian tabloid press? The general objective is to analyze the journalistic treatment of the newspaper Ojo in relation to a topic. This research is of a qualitative type, in which human processes are evaluated directly and deeply, considering the context that surrounds the object of study; likewise, it is of a descriptive level, since it identifies the most important variables; the design is non-experimental, to the extent that the phenomenon is observed in its natural state without modifying reality. The sample is made up of 11 issues of the newspaper Ojo, published between May and June 2011, on the disappearance and death of the student Ciro Castillo Rojo, chosen according to convenience. The techniques used are documentary observation, in-depth interview; the instruments are the observation guide and the questionnaire.